Isaac Olsen - lærer og forkynner - Skjelmo, Randi; Willumsen, Liv Helene (Heimen, 2017)
Source at https://doi.org/10.18261/issn.1894-3195-2017-01-05 . Accepted manuscript version, licensed CC BY-NC-ND 4.0. Isaac Olsen was a Norwegian person who went to Finnmark at the beginning of the 1700s and worked there as teacher and preacher among the Sami population until 1716. He wrote a copybook which is preserved today in the Museum of Cultural History, Norway. Parts of this copybook have been published, but the parts on which this article is based, have not been published previously. Mostly written in his own hand, the copybook contains his lectures on history and mythology as well as religious texts for teaching purposes. In addition, the book contains some official documents related to his stay in Finnmark, among other Isaac Olsen’s instructions for his work, issued by the Nidaros bishop Peder Krog, Olsen’s supplications to the Finnmark government officials and their responses to the supplications. The book also contains texts related to contemporary popular culture, such as moral stories, ghost stories and popularized religious texts. The article focuses on the way Isaac Olsen performed his work. At the time, school teaching and mission work went hand in hand, so that Isaac Olsen’s work may also be seen as mission work in Finnmark prior to the formalized mission.